Citra Pemerintah Indonesia Di Acara Pembukaan Asian Games 2018: Analisis Isi Kuantitatif Pada Situs Berita Online Tribunnews.Com, Detik.Com & Liputan6.Com - Stephanie Cecilia; Rino F. Boer; Casey Catherina (Jurnal Komunikasi, 2020)
Indonesia took the opportunity at the opening ceremony of Asian Games on 18August 2018 to show their competence and promoting the country to the world. The result of the opening ceremony was a success and received massive compliments especially from local media. The success of the opening ceremony directly affected Indonesian’s government image as the executive and as main in charge in Asian Games 2018. This objective is to know the projected government image and its similarities and differences from articles published by three most popular online news sites in Indonesia at that time that are Tribunnews.com, Detik.com and Liputan6.com using quantitative content analysis. Government image is formed from bureaucracy image and political image. The result found that political image is more dominant than bureaucracy image. This result shows that media has tendency to bring up president ex officio figures on political image, while on the bureaucracy image media has tendency to bring up all involves parties that are shows their responsibilities on the opening ceremony of Asian Games. However, tone variation on each media shown that media is not always have consistency while giving their publication, especially their publication towards government